SYNTHESIS OF A BICYCLIC GAMMA-LACTAM DIPEPTIDE ANALOG - Baldwin, J; Hulme, C; Edwards, A; Schofield, C; Parkes, K (1993)
Synthesis of a comformationally restrained bicyclic γ-lactam dipeptide mimetic, involving a diastereoselective bicyclisation reaction is described. © 1993.